Associations between dairy consumption and constipation in adults: A cross-sectional study. Issue 1 (March 2022) - Aslam, Hajara; Mohebbi, Mohammadreza; Ruusunen, Anu; Dawson, Samantha L; Williams, Lana J; Berk, Michael; Holloway-Kew, Kara L; Collier, Fiona; Loughman, Amy; Pasco, Julie A; Jacka, Felice N
Objective: The current study aimed to assess the association between dairy consumption and constipation in the general adult population. Design: Data from the Geelong Osteoporosis Study were used to assess the association between dairy consumption and constipation in women ( n =632) and men ( n =609). Information on milk, yogurt and cheese, and constipation were self-reported. Total dairy was calculated by summing the intake of milk, yogurt and cheese and expressed as servings per day. Multivariable logistic regression models adjusted for irritable bowel syndrome, major depressive disorders, mobility, body mass index, age and fibre intake were used to examine the odds ratio (OR) and 95% confidence interval (CI) between the consumption of categories of total dairy, milk, yogurt, cheese, and constipation. Results: In women, consumption of 1–2 servings/d of total dairy was associated with reduced odds for constipation (OR: 0.49; 95% CI: 0.26-0.90; P =0.021) compared to consuming <1 serving/d of total dairy after adjusting for covariates. Also, consumption of 1–4 servings/d of milk was associated with marginally reduced odds for constipation (OR: 0.63; 95% CI: 0.39-1.02; P =0.058) compared to women who consumed <1 serving/d of milk after adjusting for covariates. There were no significant associations detected between other types of dairy consumption and constipation in women, and none in men. Conclusion: In women, consumption of moderate amounts of dairy is associated with reduced odds for constipation whereas in men no associations were detected between dairy consumption and constipation. Further studies are warranted to confirm results.